Admission Blood Glucose Is Associated With the 30-Days Mortality in Septic Patients: A Retrospective Cohort Study - Wei, Xiaoyuan; Min, Yu; Yu, Jiangchuan; Wang, Qianli; Wang, Han; Li, Shuang; Su, Li (Frontiers in Medicine, 2021)
Background Sepsis, as one of the severe diseases, is frequently observed in critically ill patients, especially concurrent with diabetes. Whether admission blood glucose is associated with the prognosis and outcome of septic patients is still debatable. Methods We retrospectively reviewed and analyzed the demographic characteristics of septic patients in the Medical Information Mart for Intensive Care III (MIMIC III, version 1.4) between Jun 2001 and Oct 2012. The Chi-square and Fisher’s exact test were used for the comparison of qualitative variables among septic patients with different glucose levels and the 30-days mortality in septic patients with diabetes or not. Univariate and stepwise multivariate Cox regression analyses were used to determine the risk factors for 30-day mortality. Kaplan-Meier analysis was conducted to reveal the different 30-days survival probability in each subgroup. Results A total of 2,948 septic patients (910 cases with diabetes, 2,038 cases without diabetes) were ultimately included in the study. The 30-days mortality was 32.4% (956/2,948 cases) in the overall population without any difference among diabetic and non-diabetic septic patients (p=1.000). Admission blood glucose levels<70mg/dl was only observed to be significantly associated with the 30-days mortality of septic patients without diabetes (hazard ratio (HR)=2.48, p<0.001). After adjusting for confounders, age >65 years (HR=1.53, p=0.001), SOFA score >5 (HR=2.26, p<0.001), lactic acid>2mmol/L (Lac, HR=1.35, p=0.024), and platelet abnormality (<100k/uL: HR=1.49; >300k/uL: HR=1.36, p<0.001) were the independent risk factors for 30-days mortality in septic patients with diabetes. In non-diabetes population, age >65 years (HR=1.53, p<0.001), non-White or non-Black patients (HR=1.30, p=0.004), SOFA score >5 (HR=1.56, p<0.001), blood glucose<70mg/dl (HR=1.91, p=0.003), anion gap >2mmol/L (HR=1.60, p<0.001), Lac (HR=1.61, p<0.001), urea nitrogen>21mg/dl (HR=1.45, p=0.001), alanine aminotransferase (HR=1.31, p=0.009), total bilirubin >1.2mg/dl (HR=1.20, p=0.033), and low hemoglobin (HR=1.34, p=0.001) were the independent risk factors for 30-days mortality. Conclusions Our results indicate admission blood glucose, especially in terms of <70mg/dl, is a key signaling in predicting the worse 30-days survival probability of septic patients without diabetes, which could help clinicians to make a more suitable and precise treatment modality in dealing with septic patients.